Development of a blended teaching quality evaluation scale (BTQES) for undergraduate nursing based on the Context, Input, Process and Product (CIPP) evaluation model: A cross-sectional survey - Zhao, Yue; Li, Weijuan; Jiang, Hong; Siyiti, Mohedesi; Zhao, Meng; You, Shuping; Li, Yinglan; Yan, Ping (Nurse education in practice, 2024)
Developing a nursing undergraduate blended teaching quality evaluation tool based on the Context, Input, Process and Product model and evaluating its reliability and validity. Blended teaching is a commonly used teaching method in medical education, but there are limited tools available to effectively measure the quality of blended teaching. A Delphi study and cross-sectional study. Using the Context, Input, Process and Product model as the theoretical framework, a questionnaire was developed through literature review, expert consultation and pre-survey. From April to July 2023, 448 students from a certain university were selected as the research subjects and the questionnaire was examined for reliability and validity through a survey method. The blended teaching quality evaluation scale with 35 items includes four dimensions Context, Input, Process and Product. The content validity and reliability of the blended teaching quality evaluation scale are both good, with a content validity index of 0.934 for the total scale and a content validity index of 0.750–1.00 for each item. The SEM shows that χ2/df = 6.89, RMSEA = 0.115, CFI = 0.882, NFI=0.865, RFI= 0.855, IFI = 0.882, TLI = 0.873. The Cronbach’s α coefficient of the total scale is 0.991 and the Cronbach’s α coefficient for each dimension is 0.944–0.984. The scale is based on the characteristics of blended learning and quality evaluation covers all aspects of teaching. It can accurately evaluate the quality of teaching, evaluate the problems in the teaching process based on the teaching quality score and propose reasonable teaching improvement suggestions based on the weak links in the teaching process.